Lignocellulose-degrading enzymes production by solid-state fermentation through fungal consortium among Ascomycetes and Basidiomycetes. (January 2020) - de Oliveira Rodrigues, Patrísia; Gurgel, Leandro Vinícius Alves; Pasquini, Daniel; Badotti, Fernanda; Góes-Neto, Aristóteles; Baffi, Milla Alves
Abstract: In this study, five fungal strains ( Aspergillus niger SCBM1 – Ni, Aspergillus fumigatus SCBM6 – Fu, Trametes versicolor 561 – Tr, Ganoderma lucidum 601 – Ga and Pleurotus ostreatus PL06 – Pl) were cultivated individually and in consortium for biosynthesis of lignocellulose-degrading enzymes by solid-state fermentation (SSF). The enzyme production was investigated using a 2 5−1 fractional factorial design, with a total of 16 experiments (F1–F16) using raw sugarcane bagasse and raw wheat bran as substrates. Among the enzymatic extracts produced, Ni (F1) exhibited the highest production of endoglucanase (82.70 U/gds) (units per gram of dry substrate), exoglucanase (80.48 U/gds), β-xylosidase (145.01 U/gds) and manganese peroxidase (3.38 U/gds). For filter paper cellulase, Tr cocktail (F5) was the one that stood out (9.45 U/gds). Among the extracts produced in consortium, Ni + Tr + Pl (F6) presented the highest production of β-glucosidase (171.09 U/gds), β-xylosidase (139.99 U/gds) and manganese peroxidase (3.29 U/gds). For FPase, Ni + Fu + Ga (F12) exhibited the best production (10.46 U/gds). The highest xylanase biosynthesis (2582.38 U/gds) was obtained in Ni + Fu + Pl extract (F4). For laccase, the maximum biosynthesis (25.27 U/gds) was obtained in Tr + Ga + Pl (F13). The cocktails that presented the best enzyme production were: Ni (F1), Ni + Fu + Pl (F9), Ni + Tr + Pl (F6) and Ni + Ga + Pl (F10), demonstrating that the use of microbial consortium can be a promising alternative to obtain enzymatic cocktails with high synergism. Highlights: Fungal species were cultivated for biosynthesis of lignocellulose-degrading enzymes. A total of 16 solid-state fermentations (SSF) were carried out. Highest productions were obtained in Ni, Ni + Fu + Pl, Ni + Tr + Pl and Ni + Ga + Pl enzymatic cocktails. The fungal consortia can be a promising alternative to obtain cocktails with high synergism.